PENGARUH ELECTRONIC WORD OF MOUTH (eWOM) DAN BRAND IMAGE TERHADAP MINAT BELI PADA SKINCARE AVOSKIN BEAUTY MELALUI PLATFORM MEDIA SOSIAL TIKTOK - Hermita Putri; Riski Taufik Hidayah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research was conducted because sales of Avoskin products decreased in August 2022. In the skincare product category, Avoskin ranks fifth among local competitors. As a result, purchase intention and sales for Avoskin decreased because it was still inferior to similar competitors. The aim of this research was to determine the significant influence of the results of Electronic word of Mouth and Brand Image variables on Purchase Intention. Data collection was carried out by distributing questionnaires to 115 respondents aged 16-29 years, active TikTok social media users who knew @avoskinbeauty TikTok accounts, domiciled in JABODETABEK and Bandung City. Data testing was carried out using the SEM (Structural Equation modeling) method using SmartPLS 3.0 for Windows software. The results of the study indicate that there is a positive and significant influence between Electronic Word of Mouth and Brand Image on Purchase Intention. The research recommendation for Avoskin is to increase Purchase Intention by working with more popular TikTok influencers. In addition, if the next research uses topics related to electronic word of mouth variables, brand image, and purchase intention, it is expected to develop the use of other social media and different objects.